Eosinophilic Meningitis in an Infant - Ganesh, Ramaswamy; Janakiraman, Lalitha; Viswanathan, Venkataraman (Journal of Pediatric Neurology, 2016)
Eosinophilic meningitis is less common in children and its clinical manifestations may be different from adults. We report a 12-month-old infant who presented with irritability and bulging anterior fontanelle. His cerebrospinal fluid (CSF) analysis revealed total leucocyte count of 750 cells/mm3 (eosinophils: 20%). He was treated with corticosteroids and serial lumbar punctures. He responded well to treatment and had no neurological sequelae. At follow-up his CSF analysis showed improving trends. Eosinophiic meningitis is rare and treatment is supportive and this is probably the youngest case to be reported from India.
Keywords: infant; meningitis; eosinophils